The role of Erv1 in the mitochondrial import machinery and iron sulphur cluster export machinery in Trypanosoma brucei - Boudová, Michala (Jihočeská univerzita, 2019)
Sulfhydryl oxidase Erv1 is a ubiquitous conserved protein of the mitochondrial intermembrane space, which is implicated in mitochondrial protein import as well as in the biogenesis of iron sulphur cluster proteins. While the role of Erv1 is quite well established in higher eukaryotes, Erv1 orthologues of parasitic protists exhibit some structural peculiarities. The study presented in this thesis therefore attempted to elucidate the function of Erv1 in Trypanosoma brucei.
The role of Erv1 in the mitochondrial import machinery and iron sulphur cluster export machinery in Trypanosoma brucei